Rancang Bangun Sistem Pakar Dalam Mendeteksi Gejala Penyakit Stroke - Octavia, Bunga; M, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
At this time, Indonesia is ranked first with the highest number of stroke cases in Asia. This makes the problem of stroke in Indonesia needs special attention. Therefore, this study tried to apply the Forward Chaining method to the early detection system for stroke to see the percentage and type of stroke suffered by the user. The variables used include the types of stroke, symptom data of the types of stroke, and the certainty factor value determined by the expert. The output is the percentage and type of stroke suffered by the user. The test results show the system can produce an accurate percentage and the correct type of stroke based on the input of symptoms suffered by the user.Keywords: Certainty Factor, Bahasa C, Forward Chaining, Penyakit Stroke, Sistem Pakar